2012
DOI: 10.1371/journal.pone.0036880
|View full text |Cite
|
Sign up to set email alerts
|

Mentalizing Deficits Constrain Belief in a Personal God

Abstract: Religious believers intuitively conceptualize deities as intentional agents with mental states who anticipate and respond to human beliefs, desires and concerns. It follows that mentalizing deficits, associated with the autistic spectrum and also commonly found in men more than in women, may undermine this intuitive support and reduce belief in a personal God. Autistic adolescents expressed less belief in God than did matched neuro-typical controls (Study 1). In a Canadian student sample (Study 2), and two Ame… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
171
8
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 202 publications
(186 citation statements)
references
References 38 publications
5
171
8
2
Order By: Relevance
“…A reduced belief in God in individuals with autism has been suggested to be mediated by deficits in ToM (Norenzayan, Gervais, & Trzesniewski, 2012). This research supports the notion that ToM ability is related to religious beliefs.…”
Section: Introductionsupporting
confidence: 83%
See 1 more Smart Citation
“…A reduced belief in God in individuals with autism has been suggested to be mediated by deficits in ToM (Norenzayan, Gervais, & Trzesniewski, 2012). This research supports the notion that ToM ability is related to religious beliefs.…”
Section: Introductionsupporting
confidence: 83%
“…It is important to note that our operational definitions of empathy and emotional intelligence reflect the individual's self-reported motivations to empathize with themselves and others, whereas our definition of ToM relies on measures that assess actual ability to accurately predict the thoughts and feelings of others. The current studies use more advanced measures of ToM, rather than relying solely on the measure of empathy and the eyes tests used by Norenzayan et al (2012) and Willard and Norenzayan (2013). We first present an assessment of the same relatively low level of ToM (the Reading the Mind in the Eyes test or RMET), along with measures of empathy used by Norenzayan and colleagues to a college sample and examine the relationship with various unique measures of religiosity.…”
Section: Introductionmentioning
confidence: 99%
“…106 In a series of four studies on different populations, Ara Norenzayan et al have shown that deficits related to empathising and theory of mind, as seen in persons with autism and those tending towards autism, were associated with significantly less belief in a personal God. 107 In one such study, for instance, the participants with autism were only 11% as likely as matched normal controls to strongly endorse belief in God. But again, it is far too crude to assume that such a correlation demonstrates a determining general tendency, or implies some significant deficit on the part of all non-believers.…”
mentioning
confidence: 99%
“…Similar tendencies have been demonstrated for egocentric projection of feelings and valuations. 13 A new wrinkle in this territory, where both excess and misdirection of mentalization are found, led Ara Narenzayan et al (2012) to conclude that theism is driven by normal people's excessive propensity to assign mental states. Narenzayan began with the well-documented finding that autism involves a deficit in "theory of mind," or mental state attribution.…”
mentioning
confidence: 99%